2021
DOI: 10.1038/s41467-021-25162-w
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive insights from tertiary sulci in prefrontal cortex

Abstract: The lateral prefrontal cortex (LPFC) is disproportionately expanded in humans compared to non-human primates, although the relationship between LPFC brain structures and uniquely human cognitive skills is largely unknown. Here, we test the relationship between variability in LPFC tertiary sulcal morphology and reasoning scores in a cohort of children and adolescents. Using a data-driven approach in independent discovery and replication samples, we show that the depth of specific LPFC tertiary sulci is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
157
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(210 citation statements)
references
References 97 publications
11
157
0
Order By: Relevance
“…Thus, a shallow, short sulcus would compensate for a particularly long and deep nearby sulcus, rendering the overall degree of cortical folding within a given region approximately equal (Armstrong et al, 1995;Connolly, 1950;Zilles et al, 2013). Given this hypothesis, we propose that a relatively deeper tertiary sulcus, which may have stronger short-range white matter connections as proposed previously (Voorhies et al, 2021), may be close to sulci that are relatively shallower, thereby preserving the degree of local cortical folding. This proposal builds on a recent modification of the compensation theory of cortical folding that proposes to also incorporate local morphological features (Natu et al, 2020).…”
Section: Underlying Anatomical Mechanism(s) Likely Contributing To the Relationship Between Sulcal Depth And Human Behavior: Short-range mentioning
confidence: 57%
See 4 more Smart Citations
“…Thus, a shallow, short sulcus would compensate for a particularly long and deep nearby sulcus, rendering the overall degree of cortical folding within a given region approximately equal (Armstrong et al, 1995;Connolly, 1950;Zilles et al, 2013). Given this hypothesis, we propose that a relatively deeper tertiary sulcus, which may have stronger short-range white matter connections as proposed previously (Voorhies et al, 2021), may be close to sulci that are relatively shallower, thereby preserving the degree of local cortical folding. This proposal builds on a recent modification of the compensation theory of cortical folding that proposes to also incorporate local morphological features (Natu et al, 2020).…”
Section: Underlying Anatomical Mechanism(s) Likely Contributing To the Relationship Between Sulcal Depth And Human Behavior: Short-range mentioning
confidence: 57%
“…This normalized sulcal depth is reported in standard Freesurfer units. To assess the relation between sulcal anatomy and verbal WM performance, we applied a data-driven approach (Voorhies et al, 2021). Below, we discuss the results of our approach in which we found that a) VLPFC sulci are shallower and more variable than mid-DLPFC sulci, b) sulcal depth is related to verbal WM manipulation, c) nine left-hemisphere LPFC sulci, but no right-hemisphere LPFC sulci defined in the present study predict manipulation scores, and d) these brain-behavior relations are not generalizable, as the cortical thickness of these nine sulci is not related to verbal WM performance.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations